2021
DOI: 10.33225/pec/21.79.273
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Teacher Professional Diary on Their Reflective, Communicative and Professional Skills

Abstract: Teacher professional diaries are teacher reflections on their own and their colleagues’ observed practice. They are effective tools of increasing teacher qualification. Few research studies worldwide, while no such research studies in Georgia have been conducted on the impact of the application of reflective diaries on teachers’ reflective, communicative, and professional skills. Therefore, the aim of the research was to find out whether teachers’ reflective, communicative, and professional skills developed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Additionally, Tkavashvili (2021) in an investigative attempt examined whether teachers' reflective, communicative, and professional skills can be developed as a result of applying reflective diaries. The findings have indicated that there was a positive relationship between applying reflective diaries and the development of teachers' reflective, communicative, and professional skills.…”
Section: Features and Significance Of Reflectionmentioning
confidence: 99%
“…Additionally, Tkavashvili (2021) in an investigative attempt examined whether teachers' reflective, communicative, and professional skills can be developed as a result of applying reflective diaries. The findings have indicated that there was a positive relationship between applying reflective diaries and the development of teachers' reflective, communicative, and professional skills.…”
Section: Features and Significance Of Reflectionmentioning
confidence: 99%